Manajemen Anestesi Bebas Opioid pada Tindakan Anterior Cervical Dekompresi dengan Mieloradikulopati Cervical Spondilosis Mielopati - Prabowo, Bambang Ediwan; Ramilla, Hana Nur (Jurnal Komplikasi Anestesi, 2026)
Background: Cervical spondylotic myelopathy is degenerative pathology that occurred at spine and can caused neurologic and autonomic dysfunction. It is quite challenging in anesthesia management and to achieve the good outcome especially in maintain hemodynamic.Case: A Case-Report about 54-year-old woman with history of anterior cervical decompression, Hypertension and diabetic. She was complaining about progressive tetraplegia and hypoesthesia at level thoracal 4. The patient underwent an anterior cervical fussion due to posterior longitudinal Ligament ossification. The vital sign and hemodynamic was stable. At Induction she was given Propofol 120 mg, Dexmeditomidine 1 mcg/kgbb, Rocuronium 50 mg, paracetamol 1000 mg and ketorolac 30 mg. superfivial cervical block was done using 5 ml of Bupivacaine 0,25%. Dexmeditomidine was given at second hour prior surgery with range dose 0,7-1 mcg/kg/hour with gradual reduction of 0,2 mcg per hours. Rocuronium was given until 5th hour of surgery.Discussion: The operation lasted 6 hours with stable hemodynamics. Preoperative regulation of blood pressure and blood glucose contributed in maintaining stable haemodynamic intraoperative. In this case dexmedetomidine decreased opioid consumption intraoperative and post operative, but it might cause slight hypertension. in this case post operative outcome was good.Conclusion: Cervical spondylosis myelopathy was a degenerative condition that can cause ototnom dysfunction and neurologic disorder. Anesthesia and analgesia management plays an important role in this case. Dexmeditomidine contributed in maintaining haemodynamic patient remain stable. Careful airway management and appropriate anesthetic strategy are crucial for the successful management of patients with phlegmon and morbid obesity.